2020
DOI: 10.1177/1934578x20901409
|View full text |Cite
|
Sign up to set email alerts
|

Laminarin From Salicornia herbacea Stimulates Glucose Uptake Through AMPK-p38 MAPK Pathways in L6 Muscle Cells

Abstract: Laminarin is a component of brown seaweed, especially isolated from Salicornia herbacea. Laminarin was known to have various physiological functions, however, the molecular mechanism is still unclear. In this study, we report that laminarin stimulates an activation of AMP-activated protein kinase (AMPK) and increases glucose uptake in rat L6 myotubes. Laminarin also increases an intracellular calcium release. Inhibition of Ca2+ release, using with CaMKK inhibitor, STO-609, blocked laminarin-induced AMPK activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…It is also a dual regulator of apoptosis and cell proliferation, with antioxidant activity occurring through three mechanisms, including ROS scavenging, regulation of the antioxidant system and oxidative-stress-mediated signaling pathways [204]. In rat L6 myotubes, it has been reported that laminarin was able to activate the AMPK/p38MAPK (p38 mitogen-activated protein kinase) pathways in skeletal muscles, resulting in a better production of ATP and glucose uptake [205]. In fish muscles, β-glucans have been shown to decrease protein oxidation, lipid peroxidation and ROS levels.…”
Section: • Polysaccharidesmentioning
confidence: 99%
“…It is also a dual regulator of apoptosis and cell proliferation, with antioxidant activity occurring through three mechanisms, including ROS scavenging, regulation of the antioxidant system and oxidative-stress-mediated signaling pathways [204]. In rat L6 myotubes, it has been reported that laminarin was able to activate the AMPK/p38MAPK (p38 mitogen-activated protein kinase) pathways in skeletal muscles, resulting in a better production of ATP and glucose uptake [205]. In fish muscles, β-glucans have been shown to decrease protein oxidation, lipid peroxidation and ROS levels.…”
Section: • Polysaccharidesmentioning
confidence: 99%